Accountability issues in basic schools of Ilorin Metropolis, Kwara State, Nigeria - Ijaiya, N. Y. S.; Fasasi, Y. A.; Alabi, A. T. (penerbit ukm, 2015)
Concern for improvement in the quality of education in Nigeria, as in other countries, in recent years has raised demands for accountability from schools and particularly teachers. Using the descriptive survey design, this study examined the level of accountability among basic education teachers, strategies for promoting accountability at the basic education level and likely challenges against holding teachers responsible for their students’ learning. Twenty five officials in charge of basic education in Kwara State Ministry of Education (MOE) and State Universal Basic Education Board (SUBEB) and 30 teachers each at the primary and junior secondary schools in Ilorin Metropolis were selected as the study participants, using stratified random sampling technique. Evaluation and Accountability Questionnaire (EAQ) with reliability coefficient of .78 was used for data collection. Descriptive statistics of percentage, mean and rank-ordering were used to answer the five research questions raised in the study, while chi-square was used to test for significant difference on issues relating to accountability between educational administrators and teachers, at .05 level of significance. Findings revealed that teachers felt moderately responsible for their students’ academic performance, especially in Mathematics. Thorough supervision and use of rewards were the best measures of promoting accountability while lack of sufficient instructional aids was seen as the greatest obstacle to teachers’ accountability. It was recommended that: effective accountability policies be formulated for basic education in Nigeria with explicit rewards and sanctions; meaningful support needs to be provided for the schools, educators and students; and supervision should be all-encompassing, focused on teaching, examinations and overall students’ needs.tasty’s video